Stress among Medical Students Presented with an EEG at Suranaree University of Technology, Thailand - Areerat Siripongpan; Theeranit Namkunee; Peerapong Uthansakul; Talit Jumphoo; Pumin Duangmanee (Health Psychology Research)
# Purpose